PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN KOLASE DAUN KERING PADA ANAK KELOMPOK B DI TAMAN KANAK-KANAK MEKAR SARI BENGKULU UTARA - Misniwati; Syahrul Ismet (STKIP Subang, 2026)
This study aims to improve children's fine motor skills through collage activities using dried leaves at Mekar Sari Kindergarten, North Bengkulu. Initial observations indicated that the children's fine motor skills were not yet optimal, as evidenced by difficulties in performing physical activities involving small muscles and eye-hand coordination. This study employed a Classroom Action Research (CAR) method. The subjects of this research were children aged 4–5 years at Mekar Sari Kindergarten, North Bengkulu Regency. The sample was selected using the purposive sampling method. The research utilized the model developed by Kemmis and McTaggart. Data collection techniques included observation and documentation. Data analysis was conducted qualitatively through description and quantitatively through percentages. The results of this study indicated that the children's fine motor skills improved significantly. The percentage increased from the Pre-Cycle condition, which was in the Not Yet Developed (BB) category at 31%, to the Developed as Expected (BSH) category at 60% in Cycle I, and finally reached the success target in Cycle II within the Exceptionally Well-Developed (BSB) category at 81%.